End of the Century in Alicante. Architecture and Women Architects (1990-1999) - Gutiérrez-Mozo, María-Elia; Parra-Martínez, José; Gilsanz-Díaz, Ana (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2022)
Compared to other places, the province of Alicante is an exceptional case in the Spanish architectural scene at the end of the 20th century for both the quantity and the quality of women’s works. Well-known Alicante-based architects and internationally renowned female authors come together in this area, all of them working as a team, as a duo, but also on their own, in the most diverse disciplines and scales, from landscaping to interior design, from urban facilities to residential architecture. This article focuses on a particularly effervescent period in the construction of the (post)modernist identity of the Alicante coastline, the decade of 1990, which was crucial in the definition of both of the ways of doing and the accounts that explain or have forgotten the contribution of women to the development of the local architectural culture. The objective is triple: first a historiographic criticism of that moment from gender and generation perspectives; secondly, a cartography of women architects and their practices; and, finally, the analysis of some projects exposing differential features in their production. To do so, this paper investigates the case of the only two architects who, at the time, were already practicing alone in Alicante, Lola Alonso and Carmen Rivera. Such an inquiry reveals the parameters of an obstinate exercise of bitextuality, that is, of appropriation of the androcentric discourse, but also their unquestionable commitment to architecture.
Keywords: Alicante; Women Architects; Late modernism; Lola Alonso; Carmen Rivera; Disciplinary Commitment